A Case of Canine Renal Cell Carcinoma: an Immunohistochemical Approach - Usta, M; Ayaz, A; İlhan, F; Karaman, M; Özen, H (Journal of the Hellenic Veterinary Medical Society, 2024)
Canine Renal Cell Carcinoma (Canine RCC) is a primary renal tumor in dogs. No definitive immunohistochemical marker for this tumor is yet defined in veterinary medicine. In this case presentation, a Canine RCC detected in an 8-year-old intact male Golden Retriever was described and suitability of RCC-PN15 mouse monoclonal antibody as a diagnostic marker in this tumor was investigated. The primary tumor mass was in the right kidney and there were metastases in liver, spleen, lung, and the left kidney. Solid, tubular, and papillary subtypes of Canine RCC were noted in the primary tumor mass. In immunohistochemical staining for RCC-PN15, weak to strong immunoreactivities were observed in the primary and metastatic nodules. In this case report, RCC-PN15 was shown to be successfully used in diagnosis of Canine RCC.